The Moret Law: spaces, chances and plights of freedom in Cuba. 1870-1880. (Islas, 2022)
ABSTRACTIntroduction: This work constitutes an investigation that aims to address the freedom strategies employed by enslaved subjects in Cuba during the period of validity of the Moret Law, from 1870 to 1880.Methods: To achieve this, the historical-logical method, the index paradigm and the logical processes of analysis/synthesis and inductive/deductive were used.Results: The main result of this work is the confirmation on development of freedom strategies was present within the lines of transformation of Cuban society, in general, and in daily reality of the black masses, in particular, during the troubled 1870s.Conclusions: These strategies show the implementation of liberalism in the Spanish legal corpus of the 19.th century, which influenced the self-recognition of slaves as subjects of rights and their
Keywords: legal loophole, elites, subordination, enslaved subjects, Cuba, Moret Law.